Using Guided Reading Strategy to Improve Student’s Reading Comprehension at SMP Negeri 1 Dobo - Kahar, Siti Rahmawati; Garpenassy, Stans (MATAI: International Journal of Language Education, 2024)
The focus of this research is to study how Guided Reading Strategies can improve students' understanding at SMP Negeri 1 Dobo.This research is classroom action research which consists of four stages, namely planning, action, observation and reflection. The subjects of this research were 30 students in class VIII-9 of SMP Negeri 1 Dobo. The data collection techniques were English reading tests and interviews.The results of this study indicate that students in grades VIII-9 can improve their reading comprehension. This can be seen from the average results in pre-test (36.66), cycle I (58), and cycle II (78.66). Based on this research data, it can be concluded that the use of Guided Reading Strategies can improve reading comprehension in students in class VIII-9 of SMP Negeri 1 Dobo for the 2024/2025 academic year.